2009
DOI: 10.1902/jop.2009.080583
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Bioactive Glass Particles of Different Size Ranges to Affect Bone Formation in Interproximal Periodontal Defects in Dogs

Abstract: The bioactive glass particles of small size range underwent faster resorption and substitution by new bone than the larger particles, and the use of bioactive glass particles favored the formation of mineralized bone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 31 publications
(46 reference statements)
0
17
0
1
Order By: Relevance
“…In our study, the SiCaP investigated was identical in composition and manufacture and granule size was the only variable investigated. A study by Felipe et al10 showed distinct dissolution rates for Bioglass of different size ranges. Results from the study reported a statistically significant difference favouring bone growth adjacent to granules 300–355 μm in size when compared with those of 90–710 μm in size.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In our study, the SiCaP investigated was identical in composition and manufacture and granule size was the only variable investigated. A study by Felipe et al10 showed distinct dissolution rates for Bioglass of different size ranges. Results from the study reported a statistically significant difference favouring bone growth adjacent to granules 300–355 μm in size when compared with those of 90–710 μm in size.…”
Section: Discussionmentioning
confidence: 99%
“…Granule size is also thought to be important as it has an effect on the rate of resorption and the ability of the material to promote bone growth 8. Previous studies have shown that a minimum space of 100 μm between graft particles is essential to allow for neo‐vascularisation and bone formation and that when the spaces become larger, bone growth increases 9–11. Particle sizes of about 380 μm in diameter will yield this minimal dimension of inter‐particular space 12.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For disinfection purposes, bioactive glasses have shown no side effects in root canal therapy (19) due to several probable mechanisms, including the inhibition of bacterial colonization, a pH increase in aquatic solutions, and calcium levels (25)(26)(27). However, calcium hydroxide indicated a better antimicrobial effect than bioactive glass (28).…”
Section: Introductionmentioning
confidence: 99%